'Unsung heroes of urban transportation': architecture as environmental design in Emilio Ambasz's Taxi Project. Issue 4 (18th May 2020) - Brown, Alexandra
Abstract : Curated by architect and industrial designer Emilio Ambasz, The Museum of Modern Art's 1976 exhibition 'The Taxi Project: Realistic Solutions for Today' involved the development and display of five taxi prototypes from local and international automobile manufacturers. 'The Taxi Project' appears as a curious final act to Ambasz's time as Curator of Design at the Museum. The taxis attracted significant criticism for both utilitarian and aesthetic aspects of their design, while the location of the vehicles within the gallery space of the Museum put them quite literally beyond reach for the general public. When the prototypes failed to appear on the streets of New York after the exhibition, 'The Taxi Project' would be remembered as an ambitious, if somewhat naïve, automobile show. By circling back on Ambasz's written and exhibition-based outputs from the late 1960s, this article posits an alternative view of 'The Taxi Project' and, with it, Ambasz's approach to environmental design. It situates 'The Taxi Project' within Ambasz's almost decade-long project to reconfigure architectural production in relation to the urban environment after modernism. While the taxi was an important and effective lens through which to examine such problems, 'The Taxi Project' was never really about the cab.